Estrogen and tissue factor: exploring the interplay in menopausal females - GURJEET KAUR; VINEET AWASTHI (International Journal of Pharma and Bio Sciences, 2017)
The research conducted so far gives us ample of evidence that aging is also a discriminatory factor and is gender biased. Women undergo a symptomatic phase of menopause with growing age. A majority of studies indicate towards the low estrogen levels which lead to cascade of events deleterious for one’s health such as cardiovascular disorders. The correlation studies have been strengthening the relation of life style disorders, genetic abnormalities and autoimmune disorders with the major risk of life ie. cardiovascular disorders. The knowledge on the factors responsible for initiating and enhancing the associated risk has improved with the growing research. The present review is an attempt to widen the perspective of research by relating it with a trans-membrane glycoprotein, tissue factor and tissue factor pathway inhibitor. Tissue factor is present on the endothelial cells and in certain events in the circulatory system. Under non favorable conditions, it triggers cascade of events thus participating in the cardiovascular disorders. Tissue factor present in the extravascular compartment, acts as a hemostatic envelope contributing to the thrombus formation when the endothelial disruption takes place. The intravascular tissue factor is known to implicate in different models of thrombosis. Reports on tissue factor pathway inhibitor have also claimed to be related with the menopausal females undergoing hormone therapy. A link between tissue factor and low estrogen levels is proposed due to their known involvement in cardiovascular disorders. This provides a connecting link between the role of tissue factor, tissue factor pathway inhibitor and cardiovascular disorders. Understanding the pathways and potential biomarkers provides a promising therapeutic target in studying the treatment after effects and strategic approach towards atherosclerosis and cardiac events in the menopausal females.